Discrete and continuous simulation theory and practice - Bandyopadhyay, Susmita; Bhattacharya, Ranjan (CRC Press, Taylor & Francis Group, 2014)
When it comes to discovering glitches inherent in complex systems-be it a railway or banking, chemical production, medical, manufacturing, or inventory control system-developing a simulation of a system can identify problems with less time, effort, and disruption than it would take to employ the original. Advantageous to both academic and industrial practitioners, Discrete and Continuous Simulation: Theory and Practice offers a detailed view of simulation that is useful in several fields of study.